Water absorption and sorptivity of normal strength oil palm shell concrete - Fadhilah Hanim, Redzuan (2018)
Oil palm shell (OPS) was found to have the potential to be used as a mixing ingredient in concrete based on the attempts made by researchers to explore the potential of the palm oil industry by-products to be used in concrete industry. The attempts also made with the aim to reduce the amount of natural resources from being harvested in concrete production and to decrease the amount of waste disposed to the environment. This study was conducted to observe the durability performance of normal strength oil palm shell concrete (OPSC).The OPS was used as a replacement of coarse aggregate with different percentages which are 0%, 50% and 100% in the concrete and it was being tested for compressive test, water absorption test and sorptivity test. Fly ash was also being used as an addition for cementitious material. All the specimens were subjected to water curing for 7 and 28 days. The strength of 50% OPS (OPSC50) replacement was higher than 100% OPS (OPSC100) replacement. Meanwhile, percentage of water absorption for OPSC50 was lower than OPSC100 and it indicates that OPSC50 is better than OPSC100. However, the sorptivity of OPSC50 is higher than OPSC100. It can be concluded the right concrete mix proportion of oil palm shell, fly ash, water, superplasticizer, gravel, sand and cement content would be able to produce normal strength oil palm shell concrete.